2D gel-based Proteomics: there's life in the old dog yet. (19th October 2016) - Westermeier, Reiner
Abstract: In the nowadays mainly mass spectrometry-driven world of Proteomics, one can frequently read and hear that 2D gel-based electrophoresis methods are no longer used for proteome analysis. This short review is a compilation of facts why the gel-based workflow is not dead.